Pregnancy and Birth Outcomes among Women with Idiopathic Thrombocytopenic Purpura - Diego F. Wyszynski; Wendy J. Carman; Alan B. Cantor; John M. Graham; Liza H. Kunz; Anne M. Slavotinek; Russell S. Kirby; John Seeger (Journal of Pregnancy)
Objective. To examine pregnancy and birth outcomes among women with idiopathic thrombocytopenic purpura (ITP) or chronic ITP (cITP) diagnosed before or during pregnancy. Methods. A linkage of mothers and babies within a large US health insurance database that combines enrollment data, pharmacy claims, and medical claims was carried out to identify pregnancies in women with ITP or cITP. Outcomes included preterm birth, elective and spontaneous loss, and major congenital anomalies. Results. Results suggest that women diagnosed with ITP or cITP prior to their estimated date of conception may be at higher risk for stillbirth, fetal loss, and premature delivery. Among 446 pregnancies in women with ITP, 346 resulted in live births. Women with cITP experienced more adverse outcomes than those with a pregnancy-related diagnosis of ITP. Although 7.8% of all live births had major congenital anomalies, the majority were isolated heart defects. Among deliveries in women with cITP, 15.2% of live births were preterm. Conclusions. The results of this study provide further evidence that cause and duration of maternal ITP are important determinants of the outcomes of pregnancy.